Nalirifox in the Treatment of Metastatic Pancreatic Ductal Adenocarcinoma (mPDAC): A Comprehensive Review - J Paul, Sattwik; Lalaji, Aniket N; Shubra Saha, Sankha; Patel, Vidit; Sneha Arvind, Chauhan; Bairagi, Tanishka; Roy, Sudeshna; Patel, Ankit; Chakraborthy, G.S (Journal of Neonatal Surgery, 2025)
Background: Metastatic pancreatic ductal adenocarcinoma (mPDAC) is a highly aggressive malignancy with limited treatment options and poor survival rates. While standard chemotherapy regimens such as FOLFIRINOX and gemcitabine plus nab-paclitaxel have improved clinical outcomes, their use is often restricted due to severe toxicities. Objective: This review examines the therapeutic potential of Nalirifox, a novel combination of nanoliposomal irinotecan (nal-IRI), 5-fluorouracil (5-FU), leucovorin (LV), and oxaliplatin, in the management of mPDAC. Methods: A comprehensive evaluation of Nalirifox is provided, covering its pharmacological properties, clinical efficacy, safety profile, and comparative advantages over existing therapies. Additionally, mechanisms of resistance and potential strategies to optimize treatment outcomes are discussed. Results: Clinical evidence suggests that Nalirifox offers a promising alternative to conventional regimens, demonstrating comparable or superior efficacy with a more favorable toxicity profile. This makes it a viable option for patients who may not tolerate more aggressive chemotherapy. However, challenges such as acquired resistance and tumor microenvironment factors necessitate further investigation. Conclusion: Nalirifox represents a significant advancement in mPDAC treatment by balancing therapeutic efficacy with improved tolerability. Future research should focus on overcoming resistance mechanisms and exploring combination strategies to enhance patient outcomes.